REGIONAL LANGUAGE CULTURE IN AN EFFORT TO PRESERVE LOCAL CULTURE WHICH IS THREATENED WITH EXTINCTION AMONG THE TEENAGERS OF EAST SUMBA, MONDU VILLAGE - Loduvikus Irvan Humba Langa Andung; Munawwir Hadiwijaya (Argopuro: Jurnal Multidisiplin Ilmu Bahasa, 2024)
Language is a tool for communication used by humans in interacting. Social interaction or communication actions are carried out either directly, indirectly or symbolically. A regional language is a language spoken in a region in a national state. The use of regional languages in Indonesia is not only a means of communication but also a symbol of self-identity. The existence of regional languages will show the existence of a region's culture, because regional languages are one of the elements of culture. Language and culture are part of a society that cannot be separated, because language is the main supporter of every tradition and customs of society in Indonesia.This study explains Regional Language Culture In An Effort To Preserve The Endangered Local Culture Among The Youth Of East Sumba Mondu Village. The results of the research are that education has a great influence on the process of preserving Regional Language Culture, both family education, community and school institutions because there are a lot of cultures that are often forgotten, especially regional languages that are no longer used in daily life by teenagers, therefore it is necessary to further increase awareness teenagers with education that introduces more to the culture of the Mondu Village area. In conclusion, there is a need for greater awareness of the importance of preserving Regional Language Culture in an area, especially the Mondu Waingapu Village area because the development of the increasingly sophisticated times can cause us to forget our own culture until we realize that we will forget our own identity.